The pharmaceutical care services importance in the education and health diabetic patients recovery: an integrative review (Research, Society and Development, 2021)
Introduction: A Diabetes Mellitus (DM) is a metabolic disorder characterized by persistent hyperglycemia. It is currently a global epidemic, affecting more than 424 million individuals worldwide. Thus, the structuring of a pharmaceutical follow-up service contributes to better adherence to treatment and reduction of injuries arising from the lack of control of the pathology. Objective: To identify, through an integrative literature review, the impact of interventions performed by the pharmacist within the primary health care service on the control of clinical parameters of type II diabetes mellitus. Method: The construction of the database was carried out by the BVS Regional Portal. Experimental and non-experimental studies, published between 2015 and 2019, were included. After applying the descriptors, the total number of eligible articles found was 188 full texts, then the texts are proofreaders as appropriate to the research topic. Results: In all, eleven articles met the inclusion criteria, being them randomized, cohort studies and systematic reviews. The listed articles sought to measure the impact of interventions performed by the pharmacist, their applicability and outcome in the clinical improvement of diabetic patients. For this, laboratory tests, checking blood pressure and the presence of correlated diseases, which influence the primary clinical condition of the individual, are analyzed. Conclusion: The pharmaceutical follow-up and the interventions performed favor the control of clinical and laboratory parameters, reducing the risk of secondary complications and uncontrolled DM and related diseases.